2003
DOI: 10.1080/02844310310016758
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of the Pisiform Bone After Severe Crush Injury to the Hand

Abstract: The pisiform bone dislocated in a 56-year-old worker who had a crush injury of his wrist. Open reduction and reconstruction of the ligaments resulted in proximal subluxation of the pisiform bone and post-traumatic arthritic changes. Other authors recommend that excision of the pisiform is considered to be a more appropriate method of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
0
16
0
4
Order By: Relevance
“…Consequently total 19 articles were identified. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of these 19, 14 cases involved adults whereas 5 were of children or adolescents. Fourteen reported isolated dislocations, 1 dislocation fracture, whereas 2 cases were associated with distal radius fractures and 3 had concomitant hamate dislocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently total 19 articles were identified. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Of these 19, 14 cases involved adults whereas 5 were of children or adolescents. Fourteen reported isolated dislocations, 1 dislocation fracture, whereas 2 cases were associated with distal radius fractures and 3 had concomitant hamate dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that a careful ligamentoplasty should be performed after the excision to stabilize the FCU tendon and prevent loss of grip power. 1,15,18,21 The authors showed that careful detachment of the pisiform bone alone could have excellent functional results with rapid restoration of stability and strength.…”
Section: Discussionmentioning
confidence: 99%
“…1 Traumatic dislocation of the pisiform has only been rarely described after its initial description in 1899 by van der Donck, and since that time, Schädel-Höpfner in his review in 2003 reported only 25 radiologically confirmed cases. 2 Its rarity is because of the sturdiness of the ligamentous complex which stabilizes the pisiform to the carpus. 3 Dislocation of the pisiform in association with terrible triad injury of the elbow is an even more rare condition, with no other cases reported in the literature to our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Isolated dislocation of carpal bone has been described of which lunate dislocation is the most common isolated carpal bone dislocation. Rare patterns involve the dislocation of the scaphoid [2] pisiform [3–6] triquetrum [7] trapezium [8] trapezoid [9] capitate [10] hammate [11] and scapholunate[12] as a unit. Dislocation of the proximal row is not described in English literature.…”
Section: Introductionmentioning
confidence: 99%